The Influence of Employee Work Motivation on Work Performance at Perum Bulog in Banyuasin Regency - Januar Ida Wibowati; Hasan Pratama Putra; Nyimas Maynisa Aulia (Jurnal Ekonomi Manajemen Bisnis dan Akuntansi, 2025)
This study analyzes the Influence of Employee Work Motivation on Work Performance of Perum Bulog in Banyuasin Regency. The purpose of this study is toTo find out whether there is an influence of motivation on work performance at Perum Bulog Banyuasin and which motivational factors have the most dominant influence on employee work performance at Perum Bulog Banyuasin. The results of statistical processing, the value of the simultaneous determination coefficient of the independent variable on the dependent variable obtained (R2), amounting to 0.862 or 86.2%%, indicating that the percentage of the contribution of the influence of the independent variable on the dependent variable is 13.8%. From the results of the F test, the Sig Level value of 54.49 was obtained which is smaller than the significance level of 5% or the alpha value (α) of 0.05, which means that the variables Work motivation (X), R together have a significant influence on employee Work Performance (Y). The results obtained from the regression analysis using the SPSS version 15 tool show that there is an influence of motivation on work performance at Perum Bulog Banyuasin.